A porous conductive material, a pressure-sensitive housing, and a pressure measuring device

By using incompressible materials with Poisson's ratio of 0.45-0.55 and porous conductive materials prepared with nano-scale conductive materials, the problems of high cost and low accuracy in downhole confining pressure measurement are solved, and low-cost and high-precision downhole are achieved. Confining pressure measurement.

CN117153458BActive Publication Date: 2025-02-25CHINA NAT PETROLEUM CORP +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311109075.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-25
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

The existing technology is difficult to achieve low-cost and high-precision downhole confining pressure measurement. The traditional pressure sensor structure is large and heavy, the semiconductor pressure sensor preparation process is complex and costly, and the porous conductive flexible materials have poor adaptability in downhole confining pressure measurement.

Method used

Using an incompressible material with a Poisson's ratio of 0.45-0.55 as the porous skeleton matrix, combined with nano-scale conductive materials, a porous conductive material with micro- and nano-scale pores was prepared, and applied to the pressure-sensitive shell and pressure measurement device. .

Benefits of technology

It achieves a balance between large pressure sensing range and high sensing sensitivity, reduces production costs, improves measurement accuracy and adaptability, and is suitable for harsh downhole environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117153458B_ABST
    Figure CN117153458B_ABST
Patent Text Reader

Abstract

The present invention provides a porous conductive material, a pressure-sensitive shell and a pressure measuring device. The porous conductive material comprises a porous skeleton having micron-sized pores and nano-sized pores distributed between the micron-sized pores and a nano-sized conductive material distributed in the pores of the porous skeleton; the porous skeleton is based on an incompressible material with a Poisson's ratio of 0.45-0.55, and the matrix of the porous skeleton is distributed with nano-sized conductive materials. The pressure-sensitive shell comprises a shell body with a thickness of 1-5 mm and an encapsulation layer with a thickness of no more than 5 mm arranged on the outer surface of the shell body, the shell body encloses to form a cavity, the material of the porous conductive material is selected from the above-mentioned porous conductive material, and the material of the encapsulation layer is selected from an incompressible material with a Poisson's ratio of 0.45-0.55. The pressure measuring device comprises the above-mentioned pressure-sensitive shell, a circuit component and an electrode arranged in the cavity enclosed by the shell body of the pressure-sensitive shell; wherein the electrode is arranged on the inner surface of the shell body of the pressure-sensitive shell and connected to the circuit component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure measurement, and in particular relates to a porous conductive material, a pressure-sensitive housing and a pressure measuring device suitable for measuring underground confining pressure. Background Art

[0002] Conventional sensors generally consist of four parts: sensitive elements, conversion elements, conversion circuits, and auxiliary power supplies. The sensitive element directly senses the measured quantity and outputs a physical quantity signal that has a definite relationship with the measured quantity. The conversion element converts the physical quantity signal output by the sensitive element into an electrical signal. The conversion circuit is responsible for amplifying and modulating the electrical signal output by the conversion element. The conversion element and the conversion circuit generally require an auxiliary power supply. Pressure sensors are the most widely used sensors. Traditional pressure sensors are mainly mechanical structure devices, and the deformation of elastic elements indicates pressure. However, this structure is large and heavy, and cannot provide electrical output, so its application scenarios are greatly limited. Especially in some extreme environments, it is difficult to detect environmental pressure.

[0003] In recent years, with the development of semiconductor technology, semiconductor pressure sensors have also come into being. They are characterized by small size, light weight, high accuracy and good temperature characteristics. Especially with the development of MEMS technology, semiconductor sensors are developing towards miniaturization, with lower power consumption and higher reliability. However, its preparation process is complex and requires high precision, which makes the processing and preparation cost of this type of pressure sensor high. At the same time, due to insufficient research on basic technology and manufacturing process, some key technologies that affect reliability are difficult to break through, such as precision processing technology, sealing technology, welding technology, etc., resulting in poor reliability of miniaturized pressure sensing products, which restricts the market application of existing miniaturized sensors.

[0004] The sensing component directly determines the sensing mode, sensing range and sensitivity of the pressure sensor. The miniaturized pressure sensing component is prepared by MEMS technology, which also has the problems of high cost and high processing technology requirements, and it is difficult to realize some test scenarios for mass use. The porous conductive flexible sensing components developed in recent years have the advantages of low cost, low processing difficulty and controllable sensing range. Therefore, this type of pressure sensing component is widely used in wearable devices to achieve sensitive pressure sensing. However, the existing porous conductive flexible materials generally have the problem that large sensing range and high sensing sensitivity cannot be taken into account. The existing sensors with porous conductive flexible materials as sensing components are often not used for downhole confining pressure measurement. The reason is that the measurement environment of downhole confining pressure measurement is harsh, the downhole confining pressure is high and the sensitivity requirement of downhole confining pressure measurement is high. Limited by the structure of the existing sensors and the performance of the porous conductive flexible materials, the existing sensors with porous conductive flexible materials as sensing components have poor adaptability to downhole confining pressure measurement. At present, semiconductor pressure sensors are still commonly used in downhole confining pressure measurement, resulting in high measurement costs for downhole confining pressure measurement.

[0005] In summary, there is still a need to study technical solutions related to pressure measurement in order to achieve low-cost and high-precision downhole confining pressure measurement. Summary of the invention

[0006] The object of the present invention is to provide a porous conductive material, a pressure-sensitive housing and a pressure measuring device suitable for measuring downhole confining pressure.

[0007] In order to achieve the above objectives, the present invention provides the following five technical solutions.

[0008] In a first aspect, the present invention provides a porous conductive material, wherein the porous conductive material comprises a porous skeleton and a nanoscale conductive material distributed in the pores of the porous skeleton;

[0009] The porous skeleton uses an incompressible material with a Poisson's ratio of 0.45-0.55 as a matrix, and nano-scale conductive materials are distributed in the matrix of the porous skeleton; the porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores.

[0010] The porous conductive material provided by the present invention is used as a pressure sensing layer material, which can take into account both a large pressure sensing range and high sensing sensitivity.

[0011] According to a preferred embodiment of the first aspect, the porosity of micron-scale pores of the porous skeleton is 10%-60%.

[0012] According to a preferred embodiment of the first aspect, the porosity of the nanoscale pores of the porous framework is 10%-20%.

[0013] According to a preferred embodiment of the first aspect, the micron-sized pores of the porous skeleton have a pore size of 1 μm-1000 μm.

[0014] According to a preferred embodiment of the first aspect, the pore size of the nanoscale pores of the porous skeleton is 1 nm-1000 nm.

[0015] According to a preferred embodiment of the first aspect, based on 100% of the mass of the porous skeleton, the mass content of the nanoscale conductive material distributed in the matrix of the porous skeleton is 10%-75%.

[0016] According to a preferred embodiment of the first aspect, based on the pore volume of the porous skeleton being 100%, the volume content of the nano-scale conductive material distributed in the pores of the porous skeleton is 20%-50%.

[0017] According to a preferred embodiment of the first aspect, the porous framework is based on an incompressible material with a Poisson's ratio of 0.49-0.50.

[0018] According to a preferred embodiment of the first aspect, the porous skeleton is a flexible polymer material;

[0019] Furthermore, the porous skeleton may be, but is not limited to, a silica gel material or a rubber material;

[0020] According to a preferred embodiment of the first aspect, the nanoscale conductive material may include but is not limited to at least one of a carbon-based conductive material and a metal-based conductive material; further, the nanoscale conductive material may include but is not limited to at least one of a graphene material, a carbon nanotube material, a gold material, a silver material and a copper material.

[0021] According to a preferred embodiment of the first aspect, the nanoscale conductive material may include, but is not limited to, at least one of a granular material, a flaky material, and a fibrous material.

[0022] According to a preferred embodiment of the first aspect, the nanoscale conductive material may include, but is not limited to, at least one of carbon nanotube fibers, graphene sheets, silver nanowires, silver nanoparticles, and copper nanosheets.

[0023] According to a preferred embodiment of the first aspect, the maximum dimension of the nanoscale conductive material is 100 nm.

[0024] According to a preferred embodiment of the first aspect, the nanoscale conductive material distributed in the pores of the porous skeleton and the nanoscale conductive material distributed in the matrix of the porous skeleton can be the same or different.

[0025] According to a preferred embodiment of the first aspect, parameters of the pores and conductive particles, such as size, shape, content and distribution, etc., can be adjusted according to the requirements of measurement sensitivity and measurement range.

[0026] In a second aspect, the present invention provides a method for preparing the porous conductive material provided in the first aspect, wherein the method comprises:

[0027] The organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micron-scale pores are mixed and then cured to form;

[0028] The solidified product is subjected to a sacrificial template for making nano-scale pores and a sacrificial template for making micro-scale pores to be removed to obtain a porous skeleton;

[0029] The porous skeleton is mixed with a suspension of nano-scale conductive material, and the porous conductive material is obtained by drying.

[0030] According to a preferred embodiment of the second aspect, the sacrificial template for manufacturing nanoscale pores is made of nanoscale granular material; further, the sacrificial template for manufacturing nanoscale pores includes but is not limited to one or a combination of two or more of nanoscale water-soluble inorganic salt particles, nanoscale water-soluble organic particles and nanoscale acid-soluble metal particles; for example, nanoscale sodium chloride particles, nanoscale urea particles, and nanoscale nickel particles.

[0031] According to a preferred embodiment of the second aspect, the sacrificial template for micron-sized pores is selected from micron-sized granular materials or porous network structure materials; further, the sacrificial template for micron-sized pores includes but is not limited to one or a combination of two or more of micron-sized water-soluble inorganic salt particles, micron-sized water-soluble organic particles, micron-sized acid-soluble metal particles and acid-soluble foam metals; for example, micron-sized sodium chloride particles, micron-sized urea particles, micron-sized nickel particles, micron-sized sucrose particles, foam nickel mesh, foam aluminum mesh.

[0032] According to a preferred embodiment of the second aspect, the organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micro-scale pores are mixed, comprising:

[0033] Mixing the organic solution for preparing the incompressible material and the nano-scale conductive material to obtain a first mixture;

[0034] The sacrificial template for manufacturing nano-scale pores and the sacrificial template for manufacturing micron-scale pores are evenly arranged, and then the first mixture is poured therein; wherein the sacrificial template for manufacturing nano-scale pores is a nano-scale granular material, and the sacrificial template for manufacturing micron-scale pores is a micron-scale granular material.

[0035] According to a preferred embodiment of the second aspect, the organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micro-scale pores are mixed, comprising:

[0036] The organic solution for preparing the incompressible material, the nano-scale conductive material, and the sacrificial template for making nano-scale pores are mixed to obtain a second mixture; wherein the sacrificial template for making nano-scale pores is a nano-scale particle material;

[0037] The sacrificial template for manufacturing micron-sized pores is infiltrated with the second mixture; wherein the sacrificial template for manufacturing micron-sized pores is made of a porous network structure material.

[0038] According to a preferred embodiment of the second aspect, the organic solution for preparing the incompressible material may be, but is not limited to, an organic solution in which an incompressible material prepolymer and a curing agent are dissolved.

[0039] According to a preferred embodiment of the second aspect, the sum of the absolute volumes of the sacrificial template for making nanoscale pores and the sacrificial template for making microscale pores is 10-70% of the sum of the volumes of the organic solution and the nanoscale conductive material for preparing the incompressible material.

[0040] According to a preferred embodiment of the second aspect, the mass of the nanoscale conductive material is 1-50 wt % of the mass of the organic solution used to prepare the incompressible material.

[0041] According to a preferred embodiment of the second aspect, mixing the porous skeleton with the suspension of the nanoscale conductive material may be achieved by, but is not limited to, immersing the porous skeleton in the suspension of the nanoscale conductive material.

[0042] In a third aspect, the present invention provides a method for preparing the porous conductive material provided in the first aspect, wherein the method comprises:

[0043] Mixing the organic solution for preparing the incompressible material and the nano-scale conductive material to obtain a slurry for 3D printing;

[0044] Performing 3D printing of a porous skeleton using the 3D printing slurry;

[0045] The porous skeleton is mixed with a suspension of nano-scale conductive material, and the porous conductive material is obtained by drying.

[0046] According to a preferred embodiment of the third aspect, mixing the porous skeleton with the suspension of the nanoscale conductive material may be achieved by, but is not limited to, immersing the porous skeleton in the suspension of the nanoscale conductive material.

[0047] In a fourth aspect, the present invention provides the use of the porous conductive material provided in the first aspect as a pressure sensing layer material.

[0048] In a fifth aspect, the present invention provides a pressure-sensitive shell, which includes a shell body and an encapsulation layer arranged on the outer surface of the shell body, and the shell body is enclosed to form a cavity; wherein the material of the shell body is the porous conductive material provided in the first aspect, and the thickness of the shell body is 1mm-5mm; the material of the encapsulation layer is an incompressible material with a Poisson's ratio of 0.45-0.55, and the thickness of the encapsulation layer does not exceed 5mm.

[0049] The pressure-sensitive housing provided by the present invention is used as a housing of a pressure measuring device. In addition to the protection function of a conventional housing, it also has the pressure-sensing function of a pressure sensing layer. In a static pressure environment, the pressure compresses the internal holes of the pressure-sensitive housing, thereby strengthening the connection between the conductive particles and reducing the resistance of the pressure-sensitive housing. The pressure-sensitive housing provided by the present invention not only has the function of protecting the internal electronic devices, but also has the characteristics of high sensitivity, a large pressure sensing range, and a controllable pressure measurement range.

[0050] According to a preferred embodiment of the fifth aspect, the material of the encapsulation layer is an incompressible material with a Poisson's ratio of 0.49-0.50.

[0051] According to a preferred embodiment of the fifth aspect, the material of the encapsulation layer is a flexible polymer material;

[0052] Furthermore, the material of the encapsulation layer may be, but is not limited to, a silicone material or a rubber material.

[0053] According to a preferred embodiment of the fifth aspect, the incompressible material used for the encapsulation layer and the incompressible material used for the outer shell body may be the same or different.

[0054] In a sixth aspect, the present invention provides a pressure measuring device, which includes the pressure-sensing shell provided in the fifth aspect of the present invention, a circuit component and an electrode arranged in a cavity formed by a shell body of the pressure-sensing shell; wherein the electrode is arranged on the inner surface of the shell body of the pressure-sensing shell and connected to the circuit component.

[0055] The pressure measuring device provided by the present invention utilizes the pressure-sensitive housing provided by the present invention in combination with a circuit component disposed inside the pressure-sensitive housing, so as to realize converting the physical signal of the surrounding pressure of the external environment of the pressure measuring device into a corresponding electrical signal and storing it in a storage device in the circuit component or transmitting it to an external device for storage. It has the characteristics of low processing difficulty and low cost; at the same time, it has the characteristics of high sensitivity, large pressure sensing range and controllable pressure measuring range, which can realize a large number of uses in high surrounding pressure environments; it also has the ability to protect internal electronic devices and can be used in some harsh environments, such as oil and gas wells. The pressure measuring device provided by the present invention can be used as a pressure sensing micro-component to realize the sensing and recording of downhole pressure, and provide reliable data for oil and gas production.

[0056] According to a preferred embodiment of the sixth aspect, the electrode may be, but is not limited to, a copper electrode.

[0057] According to a preferred embodiment of the sixth aspect, the circuit component can be, but is not limited to, a circuit component used in an existing sensor using a porous conductive flexible material as a sensing component; for example, the remaining part of the circuit board component disclosed in the embodiment part of CN115127611A except the sensing module can be selected as the circuit component of the pressure measuring device of the present invention.

[0058] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0059] 1. Low cost and can meet the needs of large-scale use.

[0060] The technical solution provided by the present invention has a simple and mature preparation process and can realize low-cost industrial preparation.

[0061] 2. With large measuring range and high sensitivity, it can meet the high pressure and high precision detection requirements including downhole confining pressure.

[0062] The technical solution provided by the present invention achieves a large pressure sensing range and high sensitivity of the material by regulating the distribution of pores of different sizes and the distribution of conductive particles in a porous conductive material with an incompressible material with a Poisson's ratio close to 0.5 as a skeleton matrix.

[0063] 3. The pressure-sensing housing provided by the present invention can be combined with pressure measuring devices of various shapes.

[0064] The pressure-sensing housing provided by the present invention has a flexible structure and a wide adjustable shape range, and can be matched with pressure measuring devices of various shapes.

[0065] 4. The pressure measuring device provided by the present invention has good environmental adaptability.

[0066] The pressure measuring device provided by the present invention is provided with a pressure-sensitive housing, which has a large-range and high-sensitivity pressure sensing performance while being able to protect internal electronic components and prevent external corrosive solutions from entering the interior of the pressure measuring device, so that it can be used for high confining pressure testing in harsh environments, such as pressure testing in oil and gas wells. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a graph of the pressure sensing test data of the porous conductive material provided in Example 1.

[0068] Figure 2 This is a scanning electron microscope image of the porous conductive material provided in Example 2.

[0069] Figure 3 This is a scanning electron microscope image of the porous conductive material provided in Example 6.

[0070] Figure 4 This is a scanning electron microscope image of the porous conductive material provided in Example 8. DETAILED DESCRIPTION

[0071] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0072] Example 1

[0073] This embodiment provides a porous conductive material, which is prepared by the following method:

[0074] (1) A polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (Dow Corning Sylgard 184 PDMS and its matching curing agent are selected in this embodiment) are mixed in a weight ratio of 10:1, and n-hexane is added to dilute and increase fluidity to obtain an organic solution for preparing PDMS (wherein, based on the total volume of the polydimethylsiloxane prepolymer and the curing agent being 100%, the amount of n-hexane is 5 vol%); nanoscale conductive material carbon nanotubes with a diameter of 1-5 nm and a length of 15-30 μm are added to the organic solution for preparing PDMS (based on the total mass of the organic solution for preparing PDMS being 100%, the amount of carbon nanotubes is 10 wt%) to obtain a first mixture; nanoscale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for preparing nanoscale pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0075] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 20 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, so as to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0076] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0077] The porous skeleton uses PDMS material as a matrix, and nano-scale conductive material carbon nanotubes are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 20 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0078] (4) Using isopropanol as a solvent, adding nano-scale conductive material carbon nanotubes with a diameter of 1-5 nm and a length of 15-30 μm (the volume of the carbon nanotubes is 10 vol%, based on the total volume of isopropanol being 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the carbon nanotube suspension to the porous skeleton of 20×20×5 mm prepared in step (3) to allow the carbon nanotubes to be fully adsorbed on the pore walls of the skeleton, and then placing in an oven at 50°C to be fully dried to obtain the porous conductive material with a thickness of 5 mm.

[0079] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0080] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 5 mm, and then cured to form.

[0081] The pressure measuring device comprises a pressure-sensing housing including a housing body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) disposed on the outer surface of the housing body, a circuit component disposed in a cavity formed by the housing body of the pressure-sensing housing, and a copper electrode disposed on the inner surface of the housing body of the pressure-sensing housing and connected to the circuit component. Its pressure sensing behavior is as follows: Figure 1 shown.

[0082] Example 2

[0083] This embodiment provides a porous conductive material, which is prepared by the following method:

[0084] (1) A polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (Dow Corning Sylgard 184 PDMS and its matching curing agent are selected in this embodiment) are mixed in a weight ratio of 10:1, and n-hexane is added to dilute and increase fluidity to obtain an organic solution for preparing PDMS (wherein, the amount of n-hexane is 5 vol%, based on the total volume of the polydimethylsiloxane prepolymer and the curing agent being 100%); silver nanoparticles of nanoscale conductive material with a particle size of 50-200 nm are added to the organic solution for preparing PDMS (based on the total mass of the organic solution for preparing PDMS being 100%, the amount of silver nanoparticles is 15 wt%) to obtain a first mixture; and nanoscale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for preparing nanoscale pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0085] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 20 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, so as to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0086] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0087] The porous skeleton uses PDMS material as a matrix, and silver nanoparticles of nano-scale conductive material are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 20 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0088] (4) Using isopropanol as solvent, adding silver nanoparticles of nano-scale conductive material with a particle size of 50-200nm (the volume of silver nanoparticles is 5vol% based on the total volume of isopropanol as 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5ml of the silver nanoparticle suspension to the porous skeleton of 20×20×5mm prepared in step (3) to allow the silver nanoparticles to be fully adsorbed on the pore walls of the skeleton, and then placing it in an oven at 50°C to fully dry to obtain the porous conductive material with a thickness of 5mm. The internal silver nanoparticles are distributed as follows: Figure 2 shown.

[0089] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0090] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 1 mm, and then cured to form.

[0091] The pressure measuring device comprises a pressure-sensing housing including a housing body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) disposed on the outer surface of the housing body, a circuit component disposed in a cavity formed by the housing body of the pressure-sensing housing, and a copper electrode disposed on the inner surface of the housing body of the pressure-sensing housing and connected to the circuit component. Its pressure sensing performance is similar to that of Embodiment 1.

[0092] Example 3

[0093] This embodiment provides a porous conductive material, which is prepared by the following method:

[0094] (1) A polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (Dow Corning Sylgard 184PDMS and its matching curing agent are selected in this embodiment) are mixed in a weight ratio of 10:1, and n-hexane is added to dilute and increase fluidity to obtain an organic solution for preparing PDMS (wherein, based on the total volume of the polydimethylsiloxane prepolymer and the curing agent being 100%, the amount of n-hexane is 5 vol%); nanoscale conductive material graphene nanosheets with a microsheet size of 3-6 um and a microsheet thickness of <15 nm are added to the organic solution for preparing PDMS (based on the total mass of the organic solution for preparing PDMS being 100%, the amount of graphene is 10 wt%) to obtain a first mixture; nanoscale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for manufacturing nanoscale pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0095] (2) pouring the second mixture obtained in step (1) into a sacrificial template aluminum foam mesh (pore size 50 μm, thickness 5 mm) for making nano-scale pores, so that the aluminum foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven at room temperature for more than 30 minutes to fully exhaust the air, to ensure that the second mixture fully infiltrates the sacrificial template for making micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0096] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam aluminum mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 40%).

[0097] The porous skeleton uses PDMS material as a matrix, and nano-scale conductive material graphene is distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 40%, and the porosity of the nano-scale pores is 10%. The pore size of the micron-scale pores of the porous skeleton is 50 μm, and the pore size of the nano-scale pores is 100-500 nm.

[0098] (4) using isopropanol as a solvent, adding nano-scale conductive material graphene nanosheets with a microsheet size of 3-6 um and a microsheet thickness of <15 nm (the total volume of isopropanol is 100%, and the volume of graphene is 10 vol%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the graphene suspension to the porous skeleton with a size of 20×20×5 mm prepared in step (3) to allow the graphene to be fully adsorbed on the pore walls of the skeleton, and then placing it in an oven at 50°C to be fully dried to obtain the porous conductive material with a thickness of 5 mm.

[0099] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0100] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 1 mm, and then cured to form.

[0101] The pressure measuring device comprises a pressure-sensing shell including a shell body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) arranged on the outer surface of the shell body, a circuit component arranged in a cavity formed by the shell body of the pressure-sensing shell, and a copper electrode arranged on the inner surface of the shell body of the pressure-sensing shell and connected to the circuit component. Its pressure sensing performance is similar to that of embodiment 1, and the resistance is inversely proportional to the pressure value.

[0102] Example 4

[0103] This embodiment provides a porous conductive material, which is prepared by the following method:

[0104] (1) a polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (in this embodiment, Dow Corning Sylgard 184PDMS and its matching curing agent are selected) are mixed in a weight ratio of 10:1, and n-hexane is added to dilute and increase fluidity to obtain an organic solution for preparing PDMS (wherein, based on the total volume of the polydimethylsiloxane prepolymer and the curing agent being 100%, the amount of n-hexane is 5 vol%); silver nanowires of nanoscale conductive material with a diameter of 20-100 nm and a length of 5-15 μm are added to the organic solution for preparing PDMS (based on the total mass of the organic solution for preparing PDMS being 100%, the amount of the silver nanowires is 10 wt%) to obtain a first mixture; and nanoscale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for preparing nanoscale pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of the nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0105] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 30 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, ensuring that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0106] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 40%).

[0107] The porous skeleton uses PDMS material as a matrix, and silver nanowires of nano-scale conductive material are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 40%, and the porosity of the nano-scale pores is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 30 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0108] (4) Using isopropanol as a solvent, adding nano-scale conductive material carbon nanotubes with a diameter of 1-5 nm and a length of 15-30 μm (the volume of the carbon nanotubes is 10 vol%, based on the total volume of isopropanol being 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the carbon nanotube suspension to the porous skeleton of 20×20×5 mm prepared in step (3) to allow the carbon nanotubes to be fully adsorbed on the pore walls of the skeleton, and then placing in an oven at 50°C to be fully dried to obtain the porous conductive material of 5 mm thickness.

[0109] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0110] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 1 mm, and then cured to form.

[0111] The pressure measuring device comprises a pressure-sensing shell including a shell body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) arranged on the outer surface of the shell body, a circuit component arranged in a cavity formed by the shell body of the pressure-sensing shell, and a copper electrode arranged on the inner surface of the shell body of the pressure-sensing shell and connected to the circuit component. Its pressure sensing performance is similar to that of embodiment 1, and the resistance is inversely proportional to the pressure value.

[0112] Example 5

[0113] This embodiment provides a porous conductive material, which is prepared by the following method:

[0114] (1) A polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (Dow Corning Sylgard 184 PDMS and its matching curing agent are selected in this embodiment) are mixed in a weight ratio of 10:1, and n-hexane is added to dilute and increase fluidity to obtain an organic solution for preparing PDMS (wherein, the amount of n-hexane is 5 vol%, based on the total volume of the polydimethylsiloxane prepolymer and the curing agent being 100%); nano-scale conductive material copper nanoparticles with a particle size of 20-200 nm are added to the organic solution for preparing PDMS (based on the total mass of the organic solution for preparing PDMS being 100%, the amount of copper nanoparticles is 10 wt%) to obtain a first mixture; nano-scale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for manufacturing nano-scale pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of nano-scale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0115] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 20 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, so as to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0116] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0117] The porous skeleton uses PDMS material as a matrix, and silver nanoparticles of nano-scale conductive material are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale porosity distributed between the micron-scale pores is 30%, and the nano-scale porosity is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 20 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0118] (4) using isopropanol as a solvent, adding nano-scale conductive material copper nanoparticles with a particle size of 20-200 nm (the volume of the copper nanoparticles is 5 vol % based on the total volume of isopropanol as 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the copper nanoparticle suspension to the porous skeleton with a size of 20×20×5 mm prepared in step (3) to allow the silver nanoparticles to be fully adsorbed on the pore walls of the skeleton, and then placing in an oven at 50° C. to be fully dried to obtain the porous conductive material with a thickness of 5 mm.

[0119] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0120] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 5 mm, and then cured to form.

[0121] The pressure measuring device comprises a pressure-sensing housing including a housing body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) disposed on the outer surface of the housing body, a circuit component disposed in a cavity formed by the housing body of the pressure-sensing housing, and a copper electrode disposed on the inner surface of the housing body of the pressure-sensing housing and connected to the circuit component. Its pressure sensing performance is similar to that of Embodiment 1.

[0122] Example 6

[0123] This embodiment provides a porous conductive material, which is prepared by the following method:

[0124] (1) Mix polydimethylsiloxane (PDMS) prepolymer and a matching curing agent (Dow Corning Sylgard 184PDMS and its supporting curing agent), and adding n-hexane to dilute and increase fluidity to obtain an organic solution for PDMS preparation (wherein, based on the total volume of polydimethylsiloxane prepolymer and curing agent, the amount of n-hexane is 5 vol%); nanoscale conductive material carbon nanotubes with a diameter of 1-5nm and a length of 15-30μm are added to the organic solution for PDMS preparation (based on the total mass of the organic solution for PDMS preparation being 100%, the amount of carbon nanotubes is 10wt%) to obtain a first mixture; nanoscale sodium chloride particles with a particle size of 100-500nm as a sacrificial template for manufacturing nanoscale pores (based on the total volume of the first mixture being 100%, the amount of nanoscale sucrose particles is 10 vol%) and micron-sized sucrose particles with a particle size of 10-200μm as a sacrificial template for manufacturing micron-sized pores are added to the first mixture (based on the total volume of the first mixture being 100%, the amount of micron-sized sucrose particles is 30 vol%) to obtain a second mixture.

[0125] (2) Spin-coating the second mixture obtained in step (1) into a film with a thickness of more than 2 mm; then placing it in a vacuum drying oven at room temperature to evacuate the air for more than 30 minutes to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-sized pores; and then placing it in an oven at 70° C. overnight for full curing.

[0126] (3) placing the solidified product of step (2) in deionized water and ultrasonically removing the sacrificial template in the product to obtain a composite PDMS foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, the microscale pores are formed by the microscale sucrose particles, the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0127] The porous skeleton uses PDMS material as a matrix, and nano-scale conductive material carbon nanotubes are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 10-200 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0128] (4) Using isopropanol as solvent, add nano-scale conductive material carbon nanotubes with a diameter of 1-5nm and a length of 15-30μm (the volume of carbon nanotubes is 10vol%, based on the total volume of isopropanol as 100%), and obtain a uniform suspension after ultrasonic treatment; repeatedly add 5ml of the carbon nanotube suspension to the porous skeleton of 20×20×5mm prepared in step (3) to allow the carbon nanotubes to fully adsorb on the pore walls of the skeleton, and then place in an oven at 50°C to fully dry to obtain the porous conductive material with a thickness of 2mm. The internal morphology scanning electron microscope image is as follows Figure 3 shown.

[0129] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0130] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in this embodiment to prepare the porous conductive material) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 1 mm, and then cured to form.

[0131] The pressure measuring device comprises a pressure-sensing housing including a housing body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) disposed on the outer surface of the housing body, a circuit component disposed in a cavity formed by the housing body of the pressure-sensing housing, and a copper electrode disposed on the inner surface of the housing body of the pressure-sensing housing and connected to the circuit component. Its pressure sensing performance is similar to that of Embodiment 1.

[0132] Example 7

[0133] This embodiment provides a porous conductive material, which is prepared by the following method:

[0134] (1) adding n-hexane to Ecoflex reagent (BASF) to dilute and increase fluidity to obtain an organic solution for preparing Ecoflex silica gel (wherein, based on the total volume of the Ecoflex reagent being 100%, the amount of n-hexane is 5 vol%); adding carbon nanotubes, a nano-scale conductive material with a diameter of 1-5 nm and a length of 15-30 μm, to the organic solution for preparing Ecoflex silica gel (based on the total mass of the organic solution for preparing Ecoflex silica gel being 100%, the amount of carbon nanotubes is 10 wt%) to obtain a first mixture; adding nano-scale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for manufacturing nano-scale pores to the first mixture (based on the total volume of the first mixture being 100%, the amount of nano-scale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0135] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 20 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, so as to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0136] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite Ecoflex foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0137] The porous skeleton uses Ecoflex silica gel material as a matrix, and nano-scale conductive material carbon nanotubes are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore size of the micron-scale pores of the porous skeleton is 20μm, and the pore size of the nano-scale pores is 100-500nm.

[0138] (4) Using isopropanol as a solvent, adding nano-scale conductive material carbon nanotubes with a diameter of 1-5 nm and a length of 15-30 μm (the volume of the carbon nanotubes is 10 vol%, based on the total volume of isopropanol being 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the carbon nanotube suspension to the porous skeleton of 20×20×5 mm prepared in step (3) to allow the carbon nanotubes to be fully adsorbed on the pore walls of the skeleton, and then placing in an oven at 50°C to be fully dried to obtain the porous conductive material with a thickness of 5 mm.

[0139] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0140] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, the outer side of the porous conductive material is packaged as a whole using Ecoflex silica gel preparation organic solution (see Ecoflex silica gel preparation organic solution used in this embodiment to prepare the porous conductive material), and the packaging thickness is less than 5 mm, and then cured to form.

[0141] The pressure measuring device comprises a pressure-sensing housing including a housing body (using the porous conductive material provided in this embodiment) and an encapsulation layer (Ecoflex silicone) arranged on the outer surface of the housing body, a circuit component arranged in a cavity formed by the housing body of the pressure-sensing housing, and a copper electrode arranged on the inner surface of the housing body of the pressure-sensing housing and connected to the circuit component. The pressure sensing behavior is as follows: Figure 1 shown.

[0142] Example 8

[0143] This embodiment provides a porous conductive material, which is prepared by the following method:

[0144] (1) adding n-hexane to Ecoflex reagent (BASF) to dilute and increase fluidity to obtain an organic solution for preparing Ecoflex silica gel (wherein, based on the total volume of the Ecoflex reagent being 100%, the amount of n-hexane is 5 vol%); adding silver nanosheets of nanoscale conductive material with a thickness of 20-100 nm and a diameter of 1-30 μm to the organic solution for preparing Ecoflex silica gel (based on the total mass of the organic solution for preparing Ecoflex silica gel being 100%, the amount of the silver nanosheets is 10 wt%) to obtain a first mixture; adding nanoscale sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for manufacturing nanoscale pores to the first mixture (based on the total volume of the first mixture being 100%, the amount of the nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0145] (2) pouring the second mixture obtained in step (1) into a nickel foam mesh (pore size 20 μm, thickness 5 mm) used as a sacrificial template for manufacturing nano-scale pores, so that the nickel foam mesh is just immersed in the mixed solution; then placing it in a vacuum drying oven and evacuating the air at room temperature for more than 30 minutes to fully exhaust the air, so as to ensure that the second mixture fully infiltrates the sacrificial template for manufacturing micron-scale pores; and then placing it in an oven at 70° C. overnight for full curing.

[0146] (3) The cured product of step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite Ecoflex foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, the microscale pores are formed by the skeleton of the foam nickel mesh, the porosity of the nanoscale pores is 10%, the porosity of the microscale pores is 30%, the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh).

[0147] The porous skeleton uses Ecoflex silica gel material as a matrix, silver nanosheet particles are distributed in the matrix of the porous skeleton, and the porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore size of the micron-scale pores of the porous skeleton is 20 μm, and the pore size of the nano-scale pores is 100-500 nm.

[0148] (4) Using isopropanol as solvent, add nano-scale conductive material silver nanosheet particles with a thickness of 20-100nm and a diameter of 1-30μm (the volume of the silver nanosheet particles is 5vol%, based on the total volume of isopropanol as 100%), and obtain a uniform suspension after ultrasonic treatment; repeatedly add 5ml of the silver nanosheet particle suspension to the porous skeleton with a size of 20×20×5mm prepared in step (3) to allow the silver nanoparticles to be fully adsorbed on the pore walls of the skeleton, and then place in an oven at 50°C to fully dry to obtain the porous conductive material with a thickness of 5mm. The scanning electron microscope micrograph is shown in FIG. Figure 4 shown.

[0149] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0150] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, the outer side of the porous conductive material is packaged as a whole using Ecoflex silica gel preparation organic solution (see Ecoflex silica gel preparation organic solution used in this embodiment to prepare the porous conductive material), and the packaging thickness is less than 5 mm, and then cured to form.

[0151] The pressure measuring device comprises a pressure-sensing shell including a shell body (using the porous conductive material provided in this embodiment) and an encapsulation layer (Ecoflex silicone) arranged on the outer surface of the shell body, a circuit component arranged in a cavity formed by the shell body of the pressure-sensing shell, and a copper electrode arranged on the inner surface of the shell body of the pressure-sensing shell and connected to the circuit component. Its pressure sensing performance is similar to that of Embodiment 1.

[0152] Example 9

[0153] This embodiment provides a porous conductive material, which is prepared by the following method:

[0154] (1) adding n-hexane to Ecoflex reagent (BASF) to dilute and increase fluidity to obtain an organic solution for preparing Ecoflex silica gel (wherein, based on the total volume of the Ecoflex reagent being 100%, the amount of n-hexane is 5 vol%); adding silver nanoparticles with a particle size of 50-200 nm as a conductive material to the organic solution for preparing Ecoflex silica gel (based on the total mass of the organic solution for preparing Ecoflex silica gel being 100%, the amount of the silver nanoparticles is 10 wt%) to obtain a first mixture; adding sodium chloride particles with a particle size of 100-500 nm as a sacrificial template for manufacturing nanoscale pores to the first mixture (based on the total volume of the first mixture being 100%, the amount of the nanoscale sodium chloride particles is 10 vol%) to obtain a second mixture.

[0155] (2) First, a layer of silver particles is deposited on the surface of a nickel foam mesh (pore size 20 μm, thickness 5 mm) by using a silver mirror reaction. The specific method is as follows: first, the nickel foam mesh is cleaned and then dried, and then the nickel foam mesh is completely immersed in a solution containing silver nitrate, sodium hydroxide, glucose and ammonia water, and silver particles are pre-deposited on the surface of the nickel foam mesh by using a silver mirror reaction (the size of the silver nanoparticles is in the range of 1 nm to 100 nm, and they are bonded to the surface of the nickel foam mesh, and the thickness of the silver nanoparticle layer is close to 100 nm) to increase the conductivity of the inner wall of the pores; then, the second mixture obtained in step (1) is poured into the treated nickel foam mesh so that the nickel foam mesh is just immersed in the mixed solution; then, the mixture is placed in a vacuum drying oven at room temperature for more than 30 minutes to fully exhaust the gas, so as to ensure that the second mixture fully infiltrates the treated nickel foam mesh; and then, the mixture is placed in an oven at 70° C. overnight for full curing.

[0156] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite polyurethane foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0157] The porous skeleton uses polyurethane material as a matrix, and nano-scale conductive material carbon nanotubes are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore diameter of the micron-scale pores of the porous skeleton is 20 μm, and the pore diameter of the nano-scale pores is 100-500 nm.

[0158] (4) using isopropanol as a solvent, adding silver nanowires (diameter 20-100nm, length 5-15μm) as a nano-scale conductive material (the volume of the silver nanowires is 10vol%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5ml of the silver nanowire suspension to the porous skeleton of 20×20×5mm prepared in step (3) to allow the carbon nanotubes to be fully adsorbed on the pore walls of the skeleton, and then placing it in an oven at 50°C to fully dry to obtain the porous conductive material of 5mm thickness.

[0159] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0160] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing Ecoflex silica gel (see the organic solution for preparing the porous conductive material in this embodiment) is used to encapsulate the outer side of the porous conductive material as a whole, and the encapsulation thickness is less than 1 mm, and then cured to form.

[0161] The pressure measuring device comprises a pressure-sensing shell including a shell body (using the porous conductive material provided in this embodiment) and an encapsulation layer (Ecoflex silicone) arranged on the outer surface of the shell body, a circuit component arranged in a cavity formed by the shell body of the pressure-sensing shell, and a copper electrode arranged on the inner surface of the shell body of the pressure-sensing shell and connected to the circuit component. Its pressure sensing performance is similar to that of Embodiment 1, and the resistance size is inversely proportional to the pressure value.

[0162] Example 10

[0163] This embodiment provides a porous conductive material, which is prepared by the following method:

[0164] (1) N,N-dimethylformamide (DMF) is added to a thermoplastic polyurethane reagent (produced by BASF) and heated to 70° C. to dilute and increase fluidity to obtain an organic solution for preparing thermoplastic polyurethane (wherein, based on the total mass of the organic solution for preparing thermoplastic polyurethane, the amount of the thermoplastic polyurethane reagent is 40 wt %); silver nanoparticles with a particle size of 50-200 nm of a nano-scale conductive material are added to the organic solution for preparing thermoplastic polyurethane (based on the total mass of the organic solution for preparing thermoplastic polyurethane, the amount of the silver nanoparticles is 10 wt %) to obtain a first mixture; and nano-scale sodium chloride particles with a particle size of 100-500 nm of a sacrificial template for manufacturing nano-scale pores are added to the first mixture (based on the total volume of the first mixture as 100%, the amount of the nano-scale sodium chloride particles is 10 vol %) to obtain a second mixture.

[0165] (2) First, a layer of silver particles is deposited on the surface of a nickel foam mesh (pore size 20 μm, thickness 5 mm) by using a silver mirror reaction. The specific method is as follows: first, the nickel foam mesh is cleaned and then dried, and then the nickel foam mesh is completely immersed in a solution containing silver nitrate, sodium hydroxide, glucose and ammonia water, and silver particles are pre-deposited on the surface of the nickel foam mesh by using a silver mirror reaction (the size of the silver nanoparticles is in the range of 1 nm to 100 nm, and they are bonded to the surface of the nickel foam mesh, and the thickness of the silver nanoparticle layer is close to 100 nm) to increase the conductivity of the inner wall of the pores; then, the second mixture obtained in step (1) is poured into the treated nickel foam mesh so that the nickel foam mesh is just immersed in the mixed solution; then, the mixture is placed in a vacuum drying oven at room temperature for more than 30 minutes to fully exhaust the gas, so as to ensure that the second mixture fully infiltrates the treated nickel foam mesh; and then, the mixture is placed in an oven at 70° C. overnight for full curing.

[0166] (3) The product after curing in step (2) is placed in 0.1 mol / L dilute hydrochloric acid overnight to remove the sacrificial template in the product, thereby obtaining a composite Ecoflex foam, i.e., a porous skeleton (the nanoscale pores are formed by the added sodium chloride particles, and the microscale pores are formed by the skeleton of the foam nickel mesh; the porosity of the nanoscale pores is 10%, and the porosity of the microscale pores is 30%).

[0167] The porous skeleton uses Ecoflex silica gel material as a matrix, and nano-scale conductive material carbon nanotubes are distributed in the matrix of the porous skeleton. The porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores. The porosity of the micron-scale pores of the porous skeleton is 30%, and the porosity of the nano-scale pores is 10%. The pore size of the micron-scale pores of the porous skeleton is 20μm, and the pore size of the nano-scale pores is 100-500nm.

[0168] (4) using isopropanol as a solvent, adding silver nanowires with a diameter of 20-100 nm and a length of 5-15 μm as a nano-scale conductive material (the volume of the silver nanowires is 10 vol %, based on the total volume of the isopropanol being 100%), and obtaining a uniform suspension after ultrasonic treatment; repeatedly adding 5 ml of the silver nanowire suspension to the porous skeleton with a size of 20×20×5 mm prepared in step (3) to allow the carbon nanotubes to be fully adsorbed on the pore walls of the skeleton, and then placing it in an oven at 50° C. to be fully dried to obtain the porous conductive material with a thickness of 5 mm.

[0169] This embodiment also provides a pressure measuring device, which is prepared by the following steps:

[0170] According to the shape of the pressure sensor, the porous conductive material provided in this embodiment is cut to a suitable size, and the cut porous conductive material is coated on the outer surface of the pressure sensor as the shell of the pressure sensor, and the copper electrode is connected to the inner side of the porous conductive material and the copper electrode is connected to the circuit components inside the sensor. Then, an organic solution for preparing PDMS (see the organic solution for preparing PDMS used in preparing the porous conductive material in Example 1) is used to encapsulate the outer side of the porous conductive material as a whole, with the encapsulation thickness less than 1 mm, and then cured to form.

[0171] The pressure measuring device comprises a pressure-sensitive shell including a shell body (using the porous conductive material provided in this embodiment) and a packaging layer (PDMS) arranged on the outer surface of the shell body, a circuit component arranged in a cavity formed by the shell body of the pressure-sensitive shell, and a copper electrode arranged on the inner surface of the shell body of the pressure-sensitive shell and connected to the circuit component. The pressure sensing performance is similar to that of Embodiment 1, and the resistance size is inversely proportional to the pressure value.

Claims

1. A porous conductive material, wherein: The porous conductive material comprises a porous skeleton and a nano-scale conductive material distributed in the pores of the porous skeleton; The porous skeleton has an incompressible material with a Poisson's ratio of 0.45-0.55 as a matrix, and nano-scale conductive materials are distributed in the matrix of the porous skeleton; the porous skeleton has micron-scale pores and nano-scale pores distributed between the micron-scale pores; The porosity of the micron-scale pores of the porous skeleton is 10%-60%, and the porosity of the nano-scale pores of the porous skeleton is 10%-20%; Wherein, taking the mass of the porous skeleton as 100%, the mass content of the nano-scale conductive material distributed in the matrix of the porous skeleton is 10%-75%; taking the pore volume of the porous skeleton as 100%, the volume content of the nano-scale conductive material distributed in the pores of the porous skeleton is 20%-50%.

2. The porous conductive material according to claim 1, wherein The pore size of the micron-scale pores of the porous skeleton is 1 μm-1000 μm, and the pore size of the nano-scale pores of the porous skeleton is 1 nm-1000 nm.

3. The porous conductive material according to claim 1, wherein: The porous skeleton is based on an incompressible material with a Poisson's ratio of 0.49-0.

50.

4. The porous conductive material according to claim 1, wherein The porous skeleton is made of flexible polymer material.

5. The porous conductive material according to claim 1, wherein The maximum dimension of nanoscale conductive materials is 1000nm.

6. The method for preparing a porous conductive material according to any one of claims 1 to 5, wherein: The method includes: The organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micron-scale pores are mixed and then cured to form; The solidified product is subjected to a sacrificial template for making nano-scale pores and a sacrificial template for making micro-scale pores to be removed to obtain a porous skeleton; The porous skeleton is mixed with a suspension of nano-scale conductive material, and the porous conductive material is obtained by drying.

7. The preparation method according to claim 6, wherein: The organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micro-scale pores are mixed, including: Mixing the organic solution for preparing the incompressible material and the nano-scale conductive material to obtain a first mixture; The sacrificial template for manufacturing nano-scale pores and the sacrificial template for manufacturing micron-scale pores are evenly arranged, and then the first mixture is poured therein; wherein the sacrificial template for manufacturing nano-scale pores is a nano-scale granular material, and the sacrificial template for manufacturing micron-scale pores is a micron-scale granular material.

8. The preparation method according to claim 6, wherein: The organic solution for preparing the incompressible material, the nano-scale conductive material, the sacrificial template for making nano-scale pores, and the sacrificial template for making micro-scale pores are mixed, including: The organic solution for preparing the incompressible material, the nano-scale conductive material, and the sacrificial template for making nano-scale pores are mixed to obtain a second mixture; wherein the sacrificial template for making nano-scale pores is a nano-scale particle material; The sacrificial template for manufacturing micron-sized pores is infiltrated with the second mixture; wherein the sacrificial template for manufacturing micron-sized pores is made of a porous network structure material.

9. The preparation method according to claim 6, wherein: The sum of the absolute volumes of the sacrificial template for making nano-scale pores and the sacrificial template for making micro-scale pores is 10-70% of the sum of the volumes of the organic solution and the nano-scale conductive material used for preparing the incompressible material.

10. The preparation method according to claim 7, wherein: The mass of the nano-scale conductive material is 1-50wt% of the mass of the organic solution used for preparing the incompressible material.

11. The method for preparing a porous conductive material according to any one of claims 1 to 5, wherein: The method includes: Mixing the organic solution for preparing the incompressible material and the nano-scale conductive material to obtain a slurry for 3D printing; Performing 3D printing of a porous skeleton using the 3D printing slurry; The porous skeleton is mixed with a suspension of nano-scale conductive material, and the porous conductive material is obtained by drying.

12. Use of the porous conductive material according to any one of claims 1 to 5 as a pressure sensing layer material.

13. A pressure-sensitive housing, comprising a housing body and a packaging layer disposed on the outer surface of the housing body, wherein the housing body is enclosed to form a cavity; wherein: The material of the shell body is the porous conductive material described in any one of claims 1-5, and the thickness of the shell body is 1mm-5mm; the material of the packaging layer is an incompressible material with a Poisson's ratio of 0.45-0.55, and the thickness of the packaging layer does not exceed 5mm.

14. The pressure-sensitive housing according to claim 13, wherein: The material of the packaging layer is an incompressible material with a Poisson's ratio of 0.49-0.

50.

15. The pressure-sensitive housing according to claim 13, wherein: The material of the packaging layer is a flexible polymer material.

16. A pressure measuring device, comprising the pressure-sensing housing according to any one of claims 13 to 15, a circuit component and an electrode disposed in a cavity formed by a housing body of the pressure-sensing housing; wherein: The electrode is arranged on the inner surface of the shell body of the pressure-sensing shell and is connected to the circuit component.

Citation Information

Patent Citations

  • Shaft multi-physical field measurer

    CN115127611A

  • Porous conductive paste for preparing flexible piezoresistive sensor and preparation method and application thereof

    CN109785995A

  • Ceramic capacitive pressure sensor

    CN218724903U